"On‐Resin" Disulfide Peptide Synthesis with Methyl 3‐Nitro‐2‐pyridinesulfenate. Issue 6 (29th January 2021) - Kobayashi, Kiyotaka; Taguchi, Akihiro; Cui, Yan; Shida, Hayate; Muguruma, Kyohei; Takayama, Kentaro; Taniguchi, Atsuhiko; Hayashi, Yoshio
Abstract: New methodologies for the construction of full peptide structures with all disulfide bonds on the resin are attractive for the development of solid phase peptide synthesis. Detailed reaction conditions for the on‐resin disulfide bond formation have been investigated using a mild and chemically stable oxidizing reagent, methyl 3‐nitro‐2‐pyridinesulfenate (Npys‐OMe). Monocyclic oxytocin, MCH and bicyclic α‐conotoxin ImI were synthesized in both semi‐automated and full‐automated protocols. It was found that on‐resin intramolecular disulfide bond formation with Npys‐OMe proceeds with the minimal formation of peptide oligomers by adopting a solvent system with 0.4 M LiCl/DMF. Crude peptides with complete disulfide bond patterns can be obtained in high purity using both protocols. This minimized the RP‐HPLC purification step and the desired peptides were obtained with better yields. To our knowledge, this is the first fully automated construction of a bicyclic disulfide peptide on resin with more than 50 % purity in Fmoc‐based SPPS. These results suggest that Npys‐OMe is a useful reagent for the disulfide bond formation in automated protocols. Abstract : On‐resin disulfide bond formation using methyl 3‐nitro‐2‐pyridinesulfenate (Npys‐OMe) has been developed, leading to fully‐automated protocol for the synthesis of cyclic disulfide peptides. Using this strategy, the on‐resin synthesis of monocyclic oxytocin, melanin‐concentrating hormone and bicyclic α‐conotoxin ImI was successfully accomplished.